Tingkat Pencemaran Bakteri Escherichia Coli pada Air Tanah di Kelurahan Bidara Cina - Fakhri Nugroho Aji; Rayuna Handawati; Lia Kusumawati (Jurnal Pendidikan Geografi Undiksha, 2026)
This study aims to analyze the level of Escherichia coli (E. Coli) contamination in groundwater in Bidara Cina Sub-district East Jakarta an area characterize by high population density and frequent flooding. The research employs a quantitative descriptive method utilizing Landsat 8 satellite imagery and the Normalized Difference Built-up Index (NDBI) to assess building density alongside laboratory testing of 22 groundwater samples. The findings reveal that five samples were contaminated with Escherichia coli (E. Coli) with the highest concentration reaching 18,2/100 ml in RT 02 RW 07 – an area located very close to the Ci Liwung River and marked by extremely dense housing. Contributing factors to the contamination include recurrent flooding, poor sanitation, and domestic wastewater discharge into the river. Although located farther from the river, RW 16 also exhibited contamination due to unsanitary condition in the public housing complex. All contaminated samples exceeded the quality threshold ser by the Indonesian Ministry of Health Regulation No. 2 of 2023. These results highlight the urgent need for strengthened groundwater quality monitoring and the provision of safe altenative water sources for affected communities.